Distribution of Coliphages in Hong Kong Sewage - Dhillon, T. S. (1970)
Coliphage content of sewage collected from 11 different localities in Hong Kong was determined. The number of plaque-forming units (PFU) ranged from 0.036 × 10(3) to 15.9 × 10(3) per ml. In general, urban sewage tended to be richer than rural sewage both in PFU count as well as plaque morphological variation. Seventy-seven isolates were subjected to a host range study. Fifty per cent of these were able to grow on Escherichia coli K-12 as well as E. coli B. Approximately 32% were found to be male specific, and the remaining 18% were K-12 specific although sex-indifferent.